LEGAL ANALYSIS OF CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF MISUSE OF FACIAL AND VOICE FORGERY TECHNOLOGY IN CYBER FRAUD CRIMES IN INDONESIA - Arnold Anugerah Maharatino; Rizky Setyobowo Sagalang; Eny Susilowati; Aris Toteles (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the forms of criminal liability for the misuse of deepfake technology in cyber fraud crimes in Indonesia. The widespread use of deepfakes in the context of fraud raises legal issues because it touches on aspects of information authenticity, identity, and victim protection. The research method used is normative juridical with a statutory, conceptual, and case-based approach. The results show that the misuse of deepfakes can be qualified as a criminal act of fraud under Article 378 of the Criminal Code, and can be prosecuted under the provisions of Law Number 11 of 2008 concerning Information and Electronic Transactions and its amendments. Criminal liability of the perpetrator is based on intent, the use of digital media as a means, and the occurrence of harm to the victim. In conclusion, existing regulations still have legal gaps specifically regarding deepfakes , so normative reforms are needed to strengthen legal certainty and protect the public.